Vanadium sodium fluorophosphate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
By using sodium vanadium fluorophosphate particles and nitrogen-doped carbon coatings in the sodium ion battery positive electrode material, a uniform porous network structure is formed, and the problem of insufficient conductivity and rate performance of the existing sodium ion battery positive electrode material is solved, and excellent electrochemical performance is achieved, especially under high rate conditions.
Patent Information
- Application Number
- CN202411653245.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
The conductivity and rate performance of the existing sodium ion battery cathode materials are insufficient, which limits its reversible capacity and electrochemical performance at low magnifications.
A sodium vanadium fluorophosphate positive electrode material is used, which consists of sodium vanadium fluorophosphate particles and a nitrogen-doped carbon coating. The ratio of Ig and Id in the Raman spectrum is 1 to 1.9, the porosity is 12% to 33%, and the powder resistivity is 27,000Ω·cm to 73,000Ω·cm. Through this structure, the material forms a uniform porous network, which improves conductivity and ion diffusion.
The structural stability, conductivity and rate performance of the sodium vanadium fluorophosphate positive electrode material is significantly improved, so that it can show excellent electrochemical properties in terms of cycle performance and rate performance, especially under high-rate charge and discharge conditions.
Smart Images

Figure CN119542415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a sodium vanadium fluorophosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] With the rapid development of energy storage technology, lithium-ion batteries have become the first choice for energy storage devices in portable electronic devices, new energy vehicles and other products. However, due to the limited global lithium resources and rising prices, researchers have begun to look for alternatives to maintain sustainable energy. Sodium-ion batteries have attracted widespread attention due to their similar working principles to lithium-ion batteries, abundant sodium resources and low cost.
[0003] Among the many sodium-ion battery cathode materials, polyanionic compounds are considered to have good cycle stability due to their stable structure, especially NaVPO4F and Na3V2(PO4)2F3 (NVPF) which are frequently reported. Although NaVPO4F shows a high theoretical specific capacity, its discharge specific capacity and cycle stability are not ideal in practical applications. In contrast, NVPF has a high electronegative F - The strong inductive effect produced weakens the vanadium-oxygen covalent bond, thereby increasing the redox potential, making its average operating voltage reach about 3.9V and having a higher theoretical specific capacity of 128mA·h·g -1 However, the electronic conductivity of NVPF is extremely low, which limits its reversible capacity at low rates, thus affecting its electrochemical performance and practical application prospects in sodium-ion batteries.
[0004] To overcome these challenges, researchers have adopted a variety of strategies to improve the performance of NVPF, including ion doping, carbon coating, and constructing special morphologies to enhance the conductivity of the material, improve reaction kinetics, and improve cycle stability. However, the uniformity and stability of the sodium vanadium fluorophosphate composite materials prepared by the above methods are poor, and the electrical conductivity still needs to be improved.
[0005] Based on this, further research and development of positive electrode materials with better conductivity and rate performance are still needed to meet the increasing market demand. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a sodium vanadium fluorophosphate positive electrode material and a preparation method thereof, a positive electrode plate and a sodium ion battery, aiming to solve the technical problems of insufficient conductivity and rate performance of the positive electrode materials of sodium ion batteries in the prior art.
[0007] In the first aspect, an embodiment of the present application provides a sodium vanadium fluorophosphate positive electrode material, comprising sodium vanadium fluorophosphate particles and a nitrogen-doped carbon coating on the surface of the sodium vanadium fluorophosphate particles, the ratio of Ig to Id of the nitrogen-doped carbon coating in the Raman spectrum is 1 to 1.9, the porosity of the sodium vanadium fluorophosphate positive electrode material is 12% to 33%, and the powder resistivity of the sodium vanadium fluorophosphate positive electrode material is 27000Ω·cm to 73000Ω·cm.
[0008] In the technical solution of the embodiment of the present application, the sodium vanadium fluorophosphate positive electrode material contains a nitrogen-doped carbon coating layer, and the ratio of Ig and Id of the nitrogen-doped carbon coating layer in the Raman spectrum is controlled within the above range, and the porosity of the sodium vanadium fluorophosphate positive electrode material is controlled within the above range, so that the nitrogen-doped carbon coating layer presents a relatively uniform porous network structure, which is conducive to effectively controlling the volume change and agglomeration of the sodium vanadium fluorophosphate particles during the charge and discharge process, thereby enhancing the structural stability of the sodium vanadium fluorophosphate positive electrode material. At the same time, the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material of the present application has the above-mentioned porous amorphous carbon coating structure and the introduction of nitrogen atoms, which is conducive to controlling the powder resistivity of the sodium vanadium fluorophosphate positive electrode material within the above range, and helps to enhance the conductivity and ion diffusion of the sodium vanadium fluorophosphate positive electrode material, so that the sodium vanadium fluorophosphate positive electrode material has excellent electrochemical properties in terms of cycle performance and rate performance.
[0009] In some embodiments, the mass of carbon elements in the nitrogen-doped carbon coating layer accounts for 1% to 4% of the mass of the sodium vanadium fluorophosphate positive electrode material; the mass of nitrogen elements in the nitrogen-doped carbon coating layer accounts for 0.2% to 1.5% of the mass of the sodium vanadium fluorophosphate positive electrode material.
[0010] In this embodiment, the mass fraction of carbon element and the mass fraction of nitrogen element in the nitrogen-doped carbon coating layer are respectively controlled within the above ranges, which is conducive to the formation of a porous network structure of the nitrogen-doped carbon coating layer, more effectively improving the structural stability of the sodium vanadium fluorophosphate positive electrode material, and combined with the appropriate amount of N element doping, enhancing the conductivity and ion diffusion between the sodium vanadium fluorophosphate particles, thereby further improving the electrochemical properties of the sodium vanadium fluorophosphate positive electrode material.
[0011] In some embodiments, the D50 particle size of the sodium vanadium fluorophosphate positive electrode material is 0.8 μm to 14 μm, and the D100 particle size of the sodium vanadium fluorophosphate positive electrode material is less than 65 μm; the specific surface area of the sodium vanadium fluorophosphate positive electrode material is 12 m 2 / g~62m 2 / g; the average pore size of the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material is 1.9nm~6nm; the powder resistivity of the sodium vanadium fluorophosphate positive electrode material is 27500Ω·cm~62000Ω·cm.
[0012] In this embodiment, the electrochemical performance of the sodium vanadium fluorophosphate positive electrode material is further improved by controlling the particle size, specific surface area, powder resistivity and average pore size of the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material.
[0013] In the second aspect, an embodiment of the present application provides a method for preparing a sodium vanadium fluorophosphate positive electrode material, the preparation method comprising: mixing sodium vanadium fluorophosphate, an organic carbon source, an organic nitrogen source and a cross-linking agent, performing a gel treatment to obtain a gel slurry; performing a drying treatment and a carbonization treatment on the gel slurry to obtain a sodium vanadium fluorophosphate positive electrode material, the drying treatment comprising spray freeze drying.
[0014] In the technical scheme of the embodiment of the present application, the preparation method uses an organic carbon source and an organic nitrogen source as raw materials, combines a freeze spray drying method, and successfully prepares the above-mentioned sodium vanadium fluorophosphate positive electrode material through a sol-gel method and carbonization treatment. The preparation method can not only make the sodium vanadium fluorophosphate positive electrode material form a nitrogen-doped carbon coating layer with a uniform porous network structure, so that the porosity of the sodium vanadium fluorophosphate positive electrode material is in the range of 12% to 33%, and the ratio of Ig to Id of the nitrogen-doped carbon coating layer in the Raman spectrum is in the range of 1 to 1.9; and because the gel slurry obtained after the gel treatment is acidic, the fluoride ion is easily hydrolyzed to HF under acidic conditions, and the spray freeze drying method is used to dry the gel. It can also avoid the loss of F element caused by HF volatilization during the heating and drying process, thereby avoiding the impurities such as sodium vanadium phosphate produced by the lack of F element, and thus avoiding the increase of the powder resistivity and the decrease of the conductivity of the sodium vanadium fluorophosphate positive electrode material caused by the presence of impurities. Therefore, the sodium vanadium fluorophosphate positive electrode material prepared by the above method can maintain excellent performance during the cyclic charge-discharge process, especially under high-rate charge-discharge conditions, it can also exhibit excellent electrochemical performance.
[0015] In some embodiments, the organic carbon source is one or more of carboxymethyl cellulose, starch, sucrose and cyclodextrin; the organic nitrogen source is one or more of chitosan and gelatin; the mass ratio of the organic carbon source to the organic nitrogen source is (1:1)-(3:1); the sum of the masses of the organic carbon source and the organic nitrogen source is 6%-18% of the mass of sodium vanadium fluorophosphate.
[0016] In this embodiment, by using a specific type of organic carbon source and organic nitrogen source, the structure and morphology of the prepared sodium vanadium fluorophosphate positive electrode material can be better controlled, and the uniformity and stability of the fluorophosphate positive electrode material can be further improved, so that the conductivity and electron transfer rate of the fluorophosphate positive electrode material can be improved more significantly. Further, by controlling the amount of the organic carbon source and the organic nitrogen source, the prepared sodium vanadium fluorophosphate positive electrode material can have a suitable carbon content and nitrogen content, which is conducive to the formation of a porous network structure by the nitrogen-doped carbon coating layer, and more effectively improves the structural stability of the sodium vanadium fluorophosphate positive electrode material, and combined with the appropriate amount of doping of the N element, the conductivity and ion diffusion between the sodium vanadium fluorophosphate particles are enhanced, thereby further improving the electrochemical properties of the sodium vanadium fluorophosphate positive electrode material.
[0017] In some embodiments, the cross-linking agent is one or more of citric acid, tannic acid, tannic acid and phytic acid; the mass of the cross-linking agent is 15%-25% of the mass of sodium vanadium fluorophosphate.
[0018] In this embodiment, the cross-linking agent plays a role of cross-linking and complexing ions during the gel treatment process. Controlling the amount of the cross-linking agent added within an appropriate range is beneficial to controlling the content of carbon in the prepared sodium vanadium fluorophosphate positive electrode material and avoiding excessively high or low carbon content in the final product.
[0019] In some embodiments, the temperature of the gel treatment is 30° C.-50° C., and the time of the gel treatment is 2 h to 6 h.
[0020] In this embodiment, by controlling the temperature, time and other process conditions of the gel treatment, the organic carbon source, organic nitrogen source and cross-linking agent can more efficiently undergo gelation reaction with sodium vanadium fluorophosphate, thereby improving the performance of the final sodium vanadium fluorophosphate positive electrode material.
[0021] In some embodiments, the atomization pressure of spray freeze drying is 0.1MPa-0.4MPa; the carbonization treatment includes segmented carbonization treatment, which sequentially includes a first carbonization treatment, a second carbonization treatment and a third carbonization treatment, the temperature of the first carbonization treatment is 100℃~120℃, the insulation time of the first carbonization treatment is 2h-4h, the temperature of the second carbonization treatment is 300℃~350℃, the insulation time of the second carbonization treatment is 1h-3h, the temperature of the third carbonization treatment is 600℃~750℃, and the insulation time of the third carbonization treatment is 5-8h.
[0022] In this embodiment, by controlling the atomization pressure of spray freeze drying within the above range, the drying efficiency is improved, the loss of F element during the drying process is further reduced, and the impurities such as sodium vanadium phosphate generated due to the loss of F element are reduced, thereby improving the performance of the obtained sodium vanadium fluorophosphate positive electrode material; the segmented carbonization treatment is beneficial to the formation of a nitrogen-doped carbon coating layer with a more uniform structure.
[0023] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector and an active material layer arranged on the surface of the current collector, the active material layer comprising any one of the above-mentioned sodium vanadium fluorophosphate positive electrode materials or a sodium vanadium fluorophosphate positive electrode material prepared by any one of the above-mentioned methods for preparing the sodium vanadium fluorophosphate positive electrode materials.
[0024] In this embodiment, since the above-mentioned sodium vanadium fluorophosphate positive electrode material contains a nitrogen-doped carbon coating layer, the ratio of Ig and Id of the nitrogen-doped carbon coating layer in the Raman spectrum is controlled to be within the range of 1 to 1.9, and the porosity of the sodium vanadium fluorophosphate positive electrode material is controlled to be within the range of 12% to 33%, and the coating structure of the above-mentioned porous amorphous carbon and the introduction of nitrogen atoms are conducive to controlling the powder resistivity of the sodium vanadium fluorophosphate positive electrode material within the range of 27000Ω·cm to 73000Ω·cm, so the sodium vanadium fluorophosphate positive electrode material has good structural stability and has excellent electrochemical properties in terms of cycle performance and rate performance. Therefore, the positive electrode sheet of the present application also has good stability and excellent electrochemical properties such as cycle performance and rate performance.
[0025] In a fourth aspect, an embodiment of the present application provides a sodium ion battery, which contains the above-mentioned positive electrode plate.
[0026] In this embodiment, since the sodium ion battery includes the above-mentioned positive electrode plate, the electrochemical properties such as cycle performance and rate performance are significantly improved, especially under high rate charge-discharge conditions.
[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 A schematic diagram of the process flow of the preparation method of the sodium vanadium fluorophosphate positive electrode material of the present application;
[0030] Figure 2 This is a scanning electron microscope image of the sodium vanadium fluorophosphate positive electrode material of Example 1 of the present application;
[0031] Figure 3This is a scanning electron microscope image of the sodium vanadium fluorophosphate positive electrode material of Comparative Example 1 of the present application;
[0032] Figure 4 This is a scanning electron microscope image of the sodium vanadium fluorophosphate positive electrode material of Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0033] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0038] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0039] As analyzed in the background technology of the present application, there are technical problems in the prior art that the conductivity and rate performance of the positive electrode materials of sodium ion batteries are insufficient. In order to solve this problem, the present application provides a sodium vanadium fluorophosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery.
[0040] In the first aspect, the embodiment of the present application provides a sodium vanadium fluorophosphate positive electrode material, including sodium vanadium fluorophosphate particles and a nitrogen-doped carbon coating layer on the surface of the sodium vanadium fluorophosphate particles, the nitrogen-doped carbon coating layer has an Ig and Id ratio of 1 to 1.9 in the Raman spectrum, the porosity of the sodium vanadium fluorophosphate positive electrode material is 12% to 33%, and the powder resistivity of the sodium vanadium fluorophosphate positive electrode material is 27000Ω·cm to 73000Ω·cm
[0041] In the technical solution of the embodiment of the present application, the sodium vanadium fluorophosphate positive electrode material contains a nitrogen-doped carbon coating layer, and the ratio of Ig and Id of the nitrogen-doped carbon coating layer in the Raman spectrum is controlled within the above range, and the porosity of the sodium vanadium fluorophosphate positive electrode material is controlled within the above range, so that the nitrogen-doped carbon coating layer presents a relatively uniform porous network structure, which is conducive to effectively controlling the volume change and agglomeration of the sodium vanadium fluorophosphate particles during the charge and discharge process, thereby enhancing the structural stability of the sodium vanadium fluorophosphate positive electrode material. At the same time, the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material of the present application has the above-mentioned porous amorphous carbon coating structure and the introduction of nitrogen atoms, which is conducive to controlling the powder resistivity of the sodium vanadium fluorophosphate positive electrode material within the above range, and helps to enhance the conductivity and ion diffusion of the sodium vanadium fluorophosphate positive electrode material, so that the sodium vanadium fluorophosphate positive electrode material has excellent electrochemical properties in terms of cycle performance and rate performance.
[0042] Among them, the g peak in Raman spectrum usually refers to the peak at 1580cm- 1 Nearby peaks, for example: at 1500cm -1 -1700cm -1 The peaks in the range of 1350 cm-1 are used to characterize the graphitization degree of carbon materials, that is, to characterize the graphitization degree of nitrogen-doped carbon coatings; and the d peak usually refers to the peak at 1350 cm-1 in the Raman spectrum. -1 Nearby peaks, for example: at 1200cm -1 -1400cm -1The peaks in the range are used to characterize the defects of the carbon material, that is, to characterize the defects of the nitrogen-doped carbon coating. The ratio of Ig and Id represents the intensity ratio of the g peak and the d peak in the Raman spectrum (the value of Ig / Id), which is used to evaluate the integrity and quality of the graphite structure in the nitrogen-doped carbon coating. In the present application, the conductivity and rate performance of the positive electrode material are improved by controlling the ratio of Ig and Id in the Raman spectrum of the nitrogen-doped carbon coating on the surface of the sodium vanadium fluorophosphate positive electrode material, and combining the porosity and powder resistivity of the sodium vanadium fluorophosphate positive electrode material. Specifically, the ratio of Ig and Id in the Raman spectrum of the above-mentioned nitrogen-doped carbon coating is 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, etc., but is not limited thereto. Preferably, the ratio of Ig and Id in the Raman spectrum of the nitrogen-doped carbon coating is 1 to 1.7, more preferably 1 to 1.4.
[0043] Specifically, the porosity of the sodium vanadium fluorophosphate positive electrode material is 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, etc., and may be other values within the above range. Preferably, the porosity of the sodium vanadium fluorophosphate positive electrode material is 15% to 26%, more preferably 16% to 24%.
[0044] Specifically, the powder resistivity of the above-mentioned sodium vanadium fluorophosphate positive electrode material is 28000Ω·cm, 30000Ω·cm, 32000Ω·cm, 34000Ω·cm, 36000Ω·cm, 38000Ω·cm, 40000Ω·cm, 42000Ω·cm, 44000Ω·cm, 46000Ω·cm, 48000Ω·cm, 50000Ω·cm, 52000Ω·cm, 54000Ω·cm, 56000Ω·cm, 58000Ω·cm, 60000Ω·cm, 65000Ω·cm, 70000Ω·cm, etc., but is not limited thereto. Preferably, the powder resistivity of the above-mentioned sodium vanadium fluorophosphate positive electrode material is 27500Ω·cm to 62000Ω·cm, more preferably 27900Ω·cm to 45000Ω·cm.
[0045] In some embodiments, in order to further improve the electrochemical properties of the sodium vanadium fluorophosphate positive electrode material, the mass of the carbon element in the nitrogen-doped carbon coating layer accounts for 1% to 4% of the mass of the sodium vanadium fluorophosphate positive electrode material, which is conducive to the formation of a porous network structure by the nitrogen-doped carbon coating layer, and more effectively improves the structural stability of the sodium vanadium fluorophosphate positive electrode material; when the carbon content in the carbon coating layer is too low, the coating effect of the carbon coating layer is poor, the sodium vanadium fluorophosphate has low electronic conductivity, and the capacity is low; when the carbon content is too high, it is not conducive to ion transmission, which can easily lead to a low capacity of the finished product. Specifically, the mass of the carbon element in the nitrogen-doped carbon coating layer can account for 1%, 1.2%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, etc., of the mass of the sodium vanadium fluorophosphate positive electrode material, but is not limited to this. Preferably, the mass of the carbon element in the nitrogen-doped carbon coating layer accounts for 1.6% to 3.2% of the mass of the sodium vanadium fluorophosphate positive electrode material, and more preferably 2.1% to 3.2%.
[0046] The introduction of nitrogen atoms in the nitrogen-doped carbon coating changes the electronic structure of the porous network of the carbon aerogel, improves its electronic conductivity, helps to reduce the internal resistance of the sodium ion battery using the sodium vanadium fluorophosphate positive electrode material, improves the charge and discharge efficiency of the sodium ion battery, and enables the sodium vanadium fluorophosphate positive electrode material to maintain excellent performance during the cyclic charge and discharge process, especially under high-rate charge and discharge conditions. It can also show excellent electrochemical performance. In some embodiments, the mass of the nitrogen element in the nitrogen-doped carbon coating accounts for 0.2% to 1.5% of the mass of the sodium vanadium fluorophosphate positive electrode material. Controlling the mass of the nitrogen element in the nitrogen-doped carbon coating within the above range and appropriately changing the electronic structure of the nitrogen-doped carbon coating is conducive to further improving the electronic conductivity and ion diffusion of the sodium vanadium fluorophosphate positive electrode material, reducing the internal resistance of the sodium ion battery using the sodium vanadium fluorophosphate positive electrode material, and thereby improving the charge-discharge efficiency of the sodium ion battery. Specifically, the mass of the nitrogen element in the nitrogen-doped carbon coating layer accounts for 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, etc. of the mass of the sodium vanadium fluorophosphate positive electrode material, but is not limited thereto. Preferably, the mass of the nitrogen element in the nitrogen-doped carbon coating layer accounts for 0.4% to 0.96% of the mass of the sodium vanadium fluorophosphate positive electrode material, and more preferably 0.5% to 0.95%.
[0047] It can be understood that since the sodium vanadium fluorophosphate particles contain almost no carbon and nitrogen elements, the nitrogen content or carbon content in the above-mentioned nitrogen-doped carbon coating layer is the nitrogen content or carbon content in the sodium vanadium fluorophosphate positive electrode material of the present application.
[0048] In some embodiments, in order to further improve the performance of the sodium vanadium fluorophosphate positive electrode material, the D50 particle size of the sodium vanadium fluorophosphate positive electrode material is 0.8μm to 14μm, which can provide a more suitable diffusion path for sodium ions, and avoid the increase of the diffusion path of sodium ions due to excessive particle size, resulting in a decrease in electrochemical performance. Among them, the D50 particle size is the particle size value corresponding to the volume distribution percentage of 50% when the particle size of the sodium vanadium fluorophosphate positive electrode material is sorted from small to large. Specifically, the D50 particle size of the sodium vanadium fluorophosphate positive electrode material is 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., but not limited to this. Preferably, the D50 particle size of the sodium vanadium fluorophosphate positive electrode material is 1μm to 10μm, and more preferably, the D50 particle size of the sodium vanadium fluorophosphate positive electrode material is 2μm to 9μm. The D100 particle size of the sodium vanadium fluorophosphate positive electrode material is less than 65μm, which is conducive to further improving the performance of the sodium vanadium fluorophosphate positive electrode material. Preferably, the D100 particle size of the sodium vanadium fluorophosphate positive electrode material is 21μm to 65μm, more preferably 21μm to 35μm. Among them, the D100 particle size is the particle size value corresponding to the volume distribution percentage reaching 100% when the particle size of the sodium vanadium fluorophosphate positive electrode material is sorted from small to large. Specifically, the D100 particle size of the sodium vanadium fluorophosphate positive electrode material can be 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, 20μm, 25μm, 30μm, etc., but is not limited to this.
[0049] In some embodiments of the present application, the specific surface area of the sodium vanadium fluorophosphate positive electrode material is 12 m 2 / g~62m 2 / g, which helps to reduce the powder resistivity of the sodium vanadium fluorophosphate positive electrode material, control the specific surface area within the above range, facilitate the preparation of the positive electrode sheet, and in the drying process of the positive electrode sheet, make it easy to remove the moisture in the sodium vanadium fluorophosphate positive electrode material, thus facilitating the preparation of the positive electrode sheet and improving the performance of the positive electrode sheet. Specifically, the specific surface area of the sodium vanadium fluorophosphate positive electrode material can be 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 24m 2 / g, 26m 2 / g, 28m 2 / g, 29m 2 / g, etc., but not limited thereto. The specific surface area of the sodium vanadium fluorophosphate positive electrode material is preferably 12 m 2 / g~62m 2 / g, more preferably 12m 2 / g~30m2 / g, more preferably 19m 2 / g~30m 2 / g.
[0050] In some embodiments of the present application, the average pore size of the nitrogen-doped carbon coating layer of the above-mentioned sodium vanadium fluorophosphate positive electrode material is 1.9nm to 6nm. The nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material having the average pore size has good ion diffusivity, which is beneficial to further improve the comprehensive performance of the sodium vanadium fluorophosphate positive electrode material. Specifically, the average pore size of the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material is 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, etc., but is not limited to this. The average pore size of the nitrogen-doped carbon coating layer of the above-mentioned sodium vanadium fluorophosphate positive electrode material is preferably 3nm to 6nm.
[0051] In a second aspect, the present application provides a method for preparing a sodium vanadium fluorophosphate positive electrode material, such as Figure 1 As shown, the preparation method comprises:
[0052] S1, mixing sodium vanadium fluorophosphate, an organic carbon source, an organic nitrogen source and a cross-linking agent, and performing gel treatment to obtain a gel slurry;
[0053] S2. Drying and carbonizing the gel slurry to obtain sodium vanadium fluorophosphate positive electrode material, wherein the drying process includes spray freeze drying.
[0054] The preparation method uses an organic carbon source and an organic nitrogen source as raw materials, combines a freeze-spray drying method, and successfully prepares the sodium vanadium fluorophosphate positive electrode material as described above through a sol-gel method and a carbonization treatment. The preparation method can not only make the sodium vanadium fluorophosphate positive electrode material form a nitrogen-doped carbon coating layer with a uniform porous network structure, thereby making the porosity of the sodium vanadium fluorophosphate positive electrode material in the range of 12% to 33%, and the ratio of Ig to Id of its nitrogen-doped carbon coating layer in the Raman spectrum is in the range of 1 to 1.9; and because the gel slurry obtained after the gel treatment is acidic, the fluoride ion is easily hydrolyzed to HF under acidic conditions, and the spray freeze drying method is used to dry the gel to avoid the loss of F element caused by HF volatilization during the heating and drying process, thereby avoiding the sodium vanadium phosphate and other impurities produced by the lack of F element in the finished product, thereby avoiding the increase of the powder resistivity and the decrease of the conductivity of the sodium vanadium fluorophosphate positive electrode material caused by the presence of impurities. Therefore, the sodium vanadium fluorophosphate positive electrode material prepared by the above method can maintain excellent performance during the cyclic charge-discharge process, especially under high-rate charge and discharge conditions, it can also show excellent electrochemical performance.
[0055] The organic carbon source and organic nitrogen source can be selected from the prior art. In some embodiments, the organic carbon source is one or more of carboxymethyl cellulose, starch, sucrose and cyclodextrin. The above natural polymer material is used as a carbon source. After treatment, the surface of the obtained sodium vanadium fluorophosphate positive electrode material is coated with an amorphous carbon layer, and the primary particles are interconnected through a porous network carbon structure, which is conducive to significantly improving the performance of the sodium vanadium fluorophosphate positive electrode material.
[0056] In some embodiments, the organic nitrogen source is one or more of chitosan and gelatin. The wide source of raw materials is beneficial to reducing the manufacturing cost of the sodium vanadium fluorophosphate positive electrode material, and can better control the structure and morphology of the prepared sodium vanadium fluorophosphate positive electrode material, further improve the uniformity and stability of the material, thereby making the improvement of the conductivity and electron transfer rate of the fluorophosphate positive electrode material more significant.
[0057] In some preferred embodiments, the mass ratio of the organic carbon source to the organic nitrogen source is (1:1)-(3:1); the synergistic effect of the two can be better exerted, so that the performance of the prepared sodium vanadium fluorophosphate positive electrode material is better. Specifically, the mass ratio of the organic carbon source to the organic nitrogen source can be 1.2:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, etc., but is not limited thereto.
[0058] In some embodiments, the sum of the mass of the organic carbon source and the organic nitrogen source is 6%-18% of the mass of the sodium vanadium fluorophosphate in step S1, so that the sodium vanadium fluorophosphate positive electrode material prepared by the preparation method of the present application has a suitable carbon content and nitrogen content. As an example, the sum of the mass of the organic carbon source and the organic nitrogen source is 7%, 9%, 10%, 12%, 14%, 16%, 17%, etc. of the mass of the sodium vanadium fluorophosphate, but is not limited thereto.
[0059] The cross-linking agent plays a role of cross-linking and complexing ions during the gel treatment process, and can be selected from the prior art. In some embodiments, the cross-linking agent is one or more of citric acid, tannic acid, tannic acid and phytic acid, which plays a role of cross-linking and complexing ions, so that the prepared sodium vanadium fluorophosphate positive electrode material has better electrochemical properties.
[0060] Preferably, the mass of the cross-linking agent is 15%-25% of the mass of the sodium vanadium fluorophosphate. Controlling the amount of the cross-linking agent within this range can not only play a good role in cross-linking and complexing ions, but also control the carbon content in the sodium vanadium fluorophosphate positive electrode material to avoid the carbon content of the final product being too high or too low. As an example, the mass of the cross-linking agent is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, etc. of the mass of the sodium vanadium fluorophosphate, but is not limited thereto.
[0061] Sodium vanadium fluorophosphate used for gel treatment can be selected from the prior art or prepared by the method of the prior art, and this application has no special requirements. As an example, sodium vanadium fluorophosphate is prepared by the following method: V2O5 and H2C2O4·2H2O are mixed and dissolved in an aqueous solution according to the molar ratio of sodium vanadium fluorophosphate elements (such as 1:3), stirred at a certain temperature (such as 40°C-80°C) to become a blue solution, NaH2PO4, NaF and NH4F are dissolved in water (such as deionized water, distilled water or pure water) according to a molar ratio of 2:1:2 to form a mixed solution, and the mixed solution is poured into the above-mentioned blue solution and continuously stirred at 80°C-100°C for reaction until it is completely dissolved to form a blue-green solution, that is, a sodium vanadium fluorophosphate solution is obtained.
[0062] In some embodiments, sodium vanadium fluorophosphate is mixed with an organic carbon source, an organic nitrogen source and a cross-linking agent in the form of a sodium vanadium fluorophosphate solution for gel treatment. Of course, sodium vanadium fluorophosphate, an organic carbon source, an organic nitrogen source and a cross-linking agent can also be mixed with a solvent (such as deionized water, distilled water or pure water, etc.) for gel treatment. Those skilled in the art can select the corresponding implementation method according to specific conditions, and this application is not limited thereto.
[0063] In some embodiments, the temperature of the gel treatment is 30°C-50°C, the time of the gel treatment is 2h-6h, and the gel treatment also includes stirring, and the stirring speed is 200rpm-500rpm. In this embodiment, by controlling the temperature, time and other process conditions of the gel treatment, the organic carbon source, organic nitrogen source and cross-linking agent can be more efficiently gelated with sodium vanadium fluorophosphate, thereby improving the performance of the final product. Specifically, the temperature of the gel treatment is 35°C, 40°C, 45°C, 48°C, etc., but not limited to this; the time of the gel treatment is 2h, 3h, 4h, 5h, etc., but not limited to this; the stirring speed is 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, etc., but not limited to this.
[0064] In some embodiments, the atomization pressure of spray freeze drying is 0.1MPa-0.4MPa. By controlling the atomization pressure of spray freeze drying within the above range, the drying efficiency is improved, a nitrogen-doped carbon coating layer with a more uniform porous network structure is formed, and the loss of F during the drying process is further reduced, and the resulting impurities such as sodium vanadium phosphate are reduced, thereby improving the performance of the sodium vanadium fluorophosphate positive electrode material. Specifically, the atomization pressure of spray freeze drying can be 0.1MPa, 0.15MPa, 0.2MPa, 0.25MPa, 0.3MPa, 0.35MPa, etc., but is not limited thereto.
[0065] In some embodiments, the spray freeze drying uses a medium-micro high-pressure atomizing pump to inject the gel slurry into the atomizer at a flow rate of 1 mL / min-5 mL / min, and the inlet gas flow rate is 10 L / min-16 L / min, and the gel slurry is atomized into fine droplets, and the droplets enter the cryogenic medium container and freeze to obtain ice ball particles. In some embodiments, the cryogenic medium is one of -196°C liquid nitrogen, -80°C dry ice / ethanol, -40°C ethanol, and -20°C ethanol.
[0066] The sample after the above drying treatment is carbonized. In some embodiments, the carbonization treatment includes a staged carbonization treatment, which includes a first stage carbonization treatment, a second stage carbonization treatment and a third stage carbonization treatment in sequence. The temperature of the first stage carbonization treatment is 100°C to 120°C (for example, 105°C, 110°C, 115°C, etc.), the insulation time of the first stage carbonization treatment is 2h-4h (for example, 2.5h, 3h, 3.5h, etc.), the temperature of the second stage carbonization treatment is 300°C to 35 The temperature of the carbonization treatment is 600℃~750℃ (for example, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, etc.), and the holding time of the carbonization treatment in the third stage is 5h-8h (for example, 5.5h, 6h, 6.5h, 7h, 7.5h, etc.). The above-mentioned segmented carbonization treatment function can form a more uniform nitrogen-doped carbon coating layer. Preferably, the above-mentioned carbonization treatment is carried out in an inert gas, and the inert gas can be one or more of argon and nitrogen.
[0067] In some embodiments, the carbonized material is crushed, screened and iron-removed to obtain a sodium vanadium fluorophosphate positive electrode material, wherein the crushing method is not limited, and a jet mill or a mechanical crusher can be used for crushing. Screening is performed after crushing to improve the uniformity of the finished particles of the obtained sodium vanadium fluorophosphate positive electrode material, and to avoid the large particles in the finished product of the sodium vanadium fluorophosphate positive electrode material from having an adverse effect on the electrical properties. Preferably, the particle size range of the sodium vanadium fluorophosphate positive electrode material obtained after screening is: 0.8μm≤D50≤14μm, D100≤65μm; more preferably, the particle size range of the sodium vanadium fluorophosphate positive electrode material obtained after screening is: 1μm≤D50≤10μm, D100≤35μm.
[0068] Preferably, the humidity of the environment during crushing, screening and iron removal is controlled to be less than 15% to prevent the sodium vanadium fluorophosphate positive electrode material from absorbing too much water during the treatment process, resulting in a decrease in its electrical properties. Preferably, the content of magnetic foreign matter in the sodium vanadium fluorophosphate positive electrode material obtained after crushing, screening and iron removal is less than 150ppm, free sodium is less than 100ppm, and moisture is less than 1000ppm.
[0069] In some embodiments, the sodium vanadium fluorophosphate positive electrode material obtained by the method for preparing the sodium vanadium fluorophosphate positive electrode material provided in the present application is the sodium vanadium fluorophosphate positive electrode material as described above, and its structure, performance, etc. are not repeated here.
[0070] In a third aspect, the present application provides a positive electrode plate, comprising a current collector and an active material layer arranged on the surface of the current collector, the active material layer comprising any one of the above-mentioned sodium vanadium fluorophosphate positive electrode materials or a sodium vanadium fluorophosphate positive electrode material prepared by any of the above-mentioned methods for preparing the sodium vanadium fluorophosphate positive electrode materials.
[0071] The positive electrode plate contains the above-mentioned sodium vanadium fluorophosphate positive electrode material, and thus has good stability and excellent electrochemical properties such as cycle performance and rate performance.
[0072] In a fourth aspect, the present application provides a sodium ion battery comprising the above-mentioned positive electrode plate.
[0073] Since the sodium-ion battery contains the above-mentioned positive electrode plate, the electrochemical properties such as cycle performance and rate performance are significantly improved, especially under high-rate charge-discharge conditions, so it can be well applied in multiple usage scenarios.
[0074] In a fifth aspect, the present application provides an electrical device, comprising the sodium ion battery described above. The electrical device, such as an electric vehicle, has good power and stability due to the use of the sodium ion battery described above.
[0075] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0076] 1. Preparation method
[0077] Example 1
[0078] First, 0.5511 g of V2O5 and 1.1403 g of H2C2O4·2H2O were weighed and dissolved in 50 mL of distilled water at a molar ratio of 3:1, and stirred at 60°C for 2 h to obtain a blue VOC2O4 solution. 2.5810 g of NaH2PO4, 0.8608 g of Na2SO4, and 0.5141 g of NaF were weighed and dissolved in distilled water at a molar ratio of 3:1:2 to obtain a 50 mL solution, which was mixed with the VOC2O4 solution and heated to 100°C for condensation and reflux reaction for 8 h to convert into a blue-green solution, thereby obtaining an NVPF solution.
[0079] Then, carboxymethyl cellulose as an organic carbon source and chitosan as an organic nitrogen source were mixed in a mass ratio of 3:1. The total amount of the two added was 7% of the mass of NVPF in the NVPF solution. They were mixed and dissolved in the NVPF solution. Then, phytic acid (20% of the mass of NVPF) was added to the NVPF solution as a cross-linking agent for gel treatment. The gel treatment temperature was 50°C, the stirring speed during the process was 500 rpm, and the gel treatment time was 2 h to obtain a gel slurry.
[0080] Next, the gel slurry was pressurized by a micro high-pressure atomization pump with a pump pressure of 0.4 MPa and a flow rate of 5 mL / min. The gel slurry was injected into the atomizer with an inlet gas flow rate of 10 L / min, and the gel slurry was atomized into fine droplets. The droplets were quickly sprayed into a container filled with -196°C liquid nitrogen and were quickly frozen. The droplets were placed in a vacuum freeze dryer with a cold trap of -80°C and a vacuum degree of 8 Pa for freeze-drying for 48 hours to obtain a dry sample.
[0081] Finally, the obtained dried sample was placed in a tubular furnace and subjected to segmented carbonization treatment under high-purity argon. The procedure was insulation at 120°C for 4 hours, insulation at 350°C for 2 hours, and sintering at 750°C for 5 hours. The obtained sample was crushed, sieved and iron-removed to obtain sodium vanadium fluorophosphate positive electrode material.
[0082] The microstructure of the sodium vanadium fluorophosphate positive electrode material is as follows Figure 2 As shown in the SEM image, it can be clearly seen that the porous carbon aerogel network formed by the nitrogen-doped carbon coating layer in the sodium vanadium fluorophosphate positive electrode material prepared in Example 1 is uniformly coated on the surface of the NVPF particles. This porous structure not only provides abundant channels for the transmission of sodium ions, but also increases the surface area, thereby improving the conductivity of electrons.
[0083] Example 2
[0084] First, 0.5511 g of V2O5 and 1.1403 g of H2C2O4·2H2O were weighed and dissolved in 50 mL of distilled water at a molar ratio of 3:1, and stirred at 80 °C for 2 h to obtain a blue VOC2O4 solution. 2.5810 g of NaH2PO4, 0.8608 g of Na2SO4, and 0.5141 g of NaF were weighed and dissolved in distilled water at a molar ratio of 3:1:2 to obtain a 50 mL solution, which was mixed with the VOC2O4 solution and heated to 80 °C for condensation and reflux reaction for 8 h to convert into a blue-green solution, thus obtaining an NVPF solution.
[0085] Then, the organic carbon source sucrose and the organic nitrogen source chitosan were mixed in a mass ratio of 2:1, and the total addition amount of the two was 8% of the mass of NVPF in the NVPF solution. They were mixed and dissolved in the NVPF solution, and then 16% of the mass of NVPF tannic acid was added to the NVPF solution as a cross-linking agent for gel treatment. The gel treatment temperature was 50°C, the stirring speed during the period was 500 rpm, and the gel treatment time was 3 hours to obtain a gel slurry.
[0086] Next, the gel slurry was pressurized by a micro high-pressure atomization pump with a pump pressure of 0.1 MPa and a flow rate of 1 mL / min. The gel slurry was injected into the atomizer with an inlet gas flow rate of 16 L / min, and the gel slurry was atomized into fine droplets. The droplets were quickly sprayed into a container filled with -80°C dry ice / ethanol solution and were quickly frozen. The droplets were placed in a vacuum freeze dryer with a cold trap of -80°C and a vacuum degree of 8 Pa for freeze-drying for 48 hours to obtain a dry sample.
[0087] Finally, the obtained dried sample was placed in a tubular furnace and subjected to segmented carbonization treatment under high-purity argon. The procedure was insulation at 120°C for 2 hours, insulation at 350°C for 3 hours, and sintering at 750°C for 5 hours. The obtained sample was crushed, sieved and iron-removed to obtain sodium vanadium fluorophosphate positive electrode material.
[0088] Example 3
[0089] First, 0.5511 g of V2O5 and 1.1403 g of H2C2O4·2H2O were weighed and dissolved in 50 mL of distilled water at a molar ratio of 3:1, and stirred at 40°C for 2 h to obtain a blue VOC2O4 solution. 2.5810 g of NaH2PO4, 0.8608 g of Na2SO4, and 0.5141 g of NaF were weighed and dissolved in distilled water at a molar ratio of 3:1:2 to obtain a 50 mL solution, which was mixed with the VOC2O4 solution and heated to 90°C for 6 h to condense and reflux to convert into a blue-green solution, thus obtaining an NVPF solution.
[0090] Then, the organic carbon source cyclodextrin and the organic nitrogen source chitosan were mixed in a mass ratio of 1:1, and the total addition amount of the two was 8% of the mass of NVPF in the NVPF solution. They were mixed and dissolved in the NVPF solution, and then 15% of the mass of NVPF citric acid was added to the NVPF solution as a cross-linking agent for gel treatment. The gel treatment temperature was 50°C, the stirring speed was 400rpm, and the gel treatment time was 2h to obtain a gel slurry.
[0091] Next, the gel slurry was pressurized by a micro high-pressure atomization pump with a pump pressure of 0.1 MPa and a flow rate of 1 mL / min. The gel slurry was injected into the atomizer with an inlet gas flow rate of 16 L / min, and the gel slurry was atomized into fine droplets. The droplets were quickly sprayed into a container containing -40°C ethanol solution and were quickly frozen. The droplets were placed in a vacuum freeze dryer with a cold trap of -80°C and a vacuum degree of 8 Pa for freeze-drying for 48 hours to obtain a dry sample.
[0092] Finally, the obtained dried sample was placed in a tubular furnace and subjected to segmented carbonization treatment under high-purity nitrogen. The procedure was 120°C for 3 h, 350°C for 2 h, and 750°C for 8 h. The obtained sample was crushed, sieved, and iron-removed to obtain the sodium vanadium fluorophosphate positive electrode material.
[0093] Example 4
[0094] First, 0.5511 g of V2O5 and 1.1403 g of H2C2O4·2H2O were weighed and dissolved in 50 mL of distilled water at a molar ratio of 3:1, and stirred at 40°C for 2 h to obtain a blue VOC2O4 solution. 2.5810 g of NaH2PO4, 0.8608 g of Na2SO4, and 0.5141 g of NaF were weighed and dissolved in distilled water at a molar ratio of 3:1:2 to obtain a 50 mL solution, which was mixed with the VOC2O4 solution and heated to 80°C for 6 h to condense and reflux to convert into a blue-green solution, thereby obtaining an NVPF solution.
[0095] Then, the organic carbon source carboxymethyl cellulose and the organic nitrogen source gelatin were mixed in a mass ratio of 3:1. The total amount of the two added was 8% of the mass of NVPF in the NVPF solution. They were mixed and dissolved in the NVPF solution. Then, 16% of the mass of NVPF tannic acid was added to the NVPF solution as a cross-linking agent for gel treatment. The gel treatment temperature was 30°C, the stirring speed was 300 rpm, and the gel treatment time was 4 hours to obtain a gel slurry.
[0096] Next, the gel slurry was pressurized by a micro high-pressure atomization pump with a pump pressure of 0.2 MPa and a flow rate of 2 mL / min. The gel slurry was injected into the atomizer with an inlet gas flow rate of 12 L / min, and the gel slurry was atomized into fine droplets. The droplets were quickly sprayed into a container containing -20°C ethanol solution and were quickly frozen. The droplets were placed in a vacuum freeze dryer with a cold trap of -80°C and a vacuum degree of 8 Pa for freeze-drying for 48 hours to obtain a dry sample.
[0097] Finally, the obtained dried sample was placed in a tubular furnace and subjected to segmented carbonization treatment under high-purity argon. The procedure was insulation at 120°C for 2h, insulation at 350°C for 2h, and sintering at 750°C for 8h. The obtained sample was crushed, sieved and iron-removed to obtain sodium vanadium fluorophosphate positive electrode material.
[0098] Example 5
[0099] First, 0.5511 g of V2O5 and 1.1403 g of H2C2O4·2H2O were weighed and dissolved in 50 mL of distilled water at a molar ratio of 3:1, and stirred at 40°C for 2 h until a blue VOC2O4 solution was obtained. 2.5810 g of NaH2PO4, 0.8608 g of Na2SO4, and 0.5141 g of NaF were weighed and dissolved in distilled water at a molar ratio of 3:1:2 to obtain a 50 mL solution, which was mixed with the VOC2O4 solution and heated to 80°C for 10 h of condensation and reflux reaction to convert into a blue-green solution, thereby obtaining an NVPF solution.
[0100] Then, the organic carbon source sucrose and the organic nitrogen source gelatin were mixed in a mass ratio of 1:1, and the total amount of the two added was 8% of the mass of NVPF in the NVPF solution. They were mixed and dissolved in the NVPF solution, and then 15% of the mass of NVPF phytic acid was added to the NVPF solution for gel treatment. The gel treatment temperature was 40°C, the stirring speed was 500rpm, and the gel treatment time was 2.5h to obtain a gel slurry.
[0101] Next, the gel slurry was pressurized by a micro high-pressure atomization pump with a pump pressure of 0.3 MPa and a flow rate of 2 mL / min. The gel slurry was injected into the atomizer with an inlet gas flow rate of 14 L / min, and the gel slurry was atomized into fine droplets. The droplets were quickly sprayed into a container filled with -196°C liquid nitrogen and were quickly frozen. The droplets were placed in a vacuum freeze dryer with a cold trap of -80°C and a vacuum degree of 8 Pa for freeze-drying for 48 hours to obtain a dry sample.
[0102] Finally, the obtained dried sample was placed in a tubular furnace and subjected to segmented carbonization treatment in a high-purity nitrogen atmosphere. The procedure was insulation at 120°C for 4 hours, insulation at 350°C for 2 hours, and sintering at 750°C for 6 hours. The obtained sample was crushed, sieved and iron-removed to obtain sodium vanadium fluorophosphate positive electrode material.
[0103] Example 6
[0104] The difference from Example 1 is that the total amount of carboxymethyl cellulose, an organic carbon source, and chitosan, an organic nitrogen source, added is 20% of the mass of NVPF in the NVPF solution.
[0105] Example 7
[0106] The difference from Example 1 is that the total amount of carboxymethyl cellulose, an organic carbon source, and chitosan, an organic nitrogen source, added is 4% of the mass of NVPF in the NVPF solution.
[0107] Example 8
[0108] The difference from Example 1 is that the mass ratio of the organic carbon source carboxymethyl cellulose and the organic nitrogen source chitosan is 5:1.
[0109] Example 9
[0110] The difference from Example 1 is that the mass ratio of the organic carbon source carboxymethyl cellulose and the organic nitrogen source chitosan is 1:2.
[0111] Example 10
[0112] The difference from Example 1 is that the gel slurry is pressurized by a micro high-pressure atomizing pump with a pump pressure of 0.2 MPa, and the gel slurry is injected into the atomizer at a flow rate of 14 mL / min, and the inlet gas flow rate is 8 L / min.
[0113] Embodiment 11
[0114] One of the differences from Example 1 is that the gel slurry is pressurized by a micro high-pressure atomizing pump with a pump pressure of 0.6 MPa, and the gel slurry is injected into the atomizer at a flow rate of 6 mL / min, and the inlet gas flow rate is 15 L / min.
[0115] The second is to put the obtained dried sample into a tubular furnace and perform a segmented carbonization treatment under high-purity argon gas, with the procedure of keeping at 120°C for 4h, keeping at 350°C for 2h, and sintering at 650°C for 5h.
[0116] Example 12
[0117] The difference from Example 1 is that the obtained dried sample is placed in a tubular furnace and subjected to a staged carbonization treatment under high-purity argon gas, with the procedure of keeping at 120°C for 2h, rapidly heating to 750°C at a rate of 10°C / min, and sintering at 750°C for 2h.
[0118] Comparative Example 1
[0119] The difference from Example 1 is that after the gel rubber is atomized, a high-temperature gas gel atomized particle with a temperature exceeding 120°C is used instead of rapid freezing and freeze drying, and a dry sample is obtained by spray drying. The remaining steps are the same as in Example 1 to prepare sodium vanadium fluorophosphate positive electrode material.
[0120] The microstructure of the sodium vanadium fluorophosphate positive electrode material is as follows Figure 3 As shown in the figure, the non-porous carbon layer formed on its surface simply covers the surface of the NVPF particles, forming a relatively smooth and agglomerated carbon layer. Although this structure also plays a certain protective role, its ion and electron transmission performance is poorer than that of the porous carbon aerogel coating.
[0121] Comparative Example 2
[0122] The difference from Example 1 is that the gel slurry is directly dried in a vacuum drying oven at 80° C. for 10 h to obtain a dry sample, and the remaining steps are the same as those in Example 1 to prepare a nitrogen-doped carbon aerogel-coated sodium vanadium fluorophosphate positive electrode material.
[0123] The microstructure of the sodium vanadium fluorophosphate positive electrode material is as follows Figure 4 As shown. The porous carbon obtained by vacuum drying technology in this comparative example is simply mixed with NVPF particles without forming an obvious coating layer. Although this structure can introduce the advantages of porous carbon, due to the lack of a clear coating layer, its structural stability and ion / electron transport performance are not as good as the nitrogen-doped carbon coating layer in the sodium vanadium fluorophosphate positive electrode material obtained in the example.
[0124] 2. Test Method
[0125] 1. Property test of sodium vanadium fluorophosphate positive electrode material
[0126] Carbon content test: Use carbon sulfur meter to test.
[0127] Nitrogen content test: The N content is determined by an element analyzer using a high-temperature combustion method, referring to standard GB / T37588-2019.
[0128] Particle size test: The laser particle size analyzer is used to measure the particle size by measuring the intensity of scattered light generated when the laser beam passes through the dispersed particle sample. The particle size distribution is obtained by analyzing and calculating the scattered light spectrum formed.
[0129] Specific surface area test: The gas adsorption BET method is used, with nitrogen as the adsorbent and helium as the carrier gas. When the mixed gas flows through the solid material, the solid material physically adsorbs the nitrogen at low temperature, while the carrier gas is not adsorbed. The adsorption amount under different relative pressures is measured to calculate the specific surface area.
[0130] Average pore size test: observed and calculated using SEM.
[0131] I D / I G :Test the Raman spectrum of the sample to be tested, according to the intensity of D peak I D The intensity of the G peak I G Calculate I D / I G The specific test method is: use a medicine spoon to take 10 mg of sample in the middle of the slide, take another slide and press it on the sample, press for a while, and press the slide into a tablet without dispersion. The measurement range is 50-4000nm, and the laser is 405 nm.
[0132] Porosity test method: refer to TCSTM 00553-2022, Porosity determination method for lightweight porous materials
[0133] Powder resistivity: tested using the four-probe method at a pressure of 10 MPa.
[0134] The sodium ion diffusion coefficient was measured by electrochemical impedance spectroscopy (EIS).
[0135] The test results of the above tests of the sodium vanadium fluorophosphate positive electrode materials prepared in various embodiments and comparative examples are listed in the following Table 1.
[0136] 2. Electrochemical performance test
[0137] The sodium vanadium fluorophosphate positive electrode material prepared in the above embodiment and the positive electrode material prepared in the comparative example are mixed with conductive carbon black (Super P) and polyvinylidene fluoride PVDF at a mass ratio of 7:2:1, dispersed in N-methyl-2-pyrrolidone NMP solvent to form a uniform slurry, and coated on aluminum foil using a scraper or a four-sided coater to form a positive electrode sheet. Then, the slurry is coated on the aluminum foil current collector using a sheet maker to form a 150nm thick film layer, and vacuum dried at 120°C for 8 hours, and then the aluminum foil coated with the material is cut into a circular electrode sheet with a diameter of 12mm to assemble into a CR2032 button battery. A metal sodium sheet is used as the counter electrode, and an electrolyte with 1 M NaClO4 as the solute is used. The electrolyte is a mixture of propylene carbonate and ethylene carbonate in a volume ratio of 1:1, and contains 5% by mass of fluoroethylene carbonate as an additive. The diaphragm uses Whatman glass fiber.
[0138] The electrochemical performance was evaluated by constant current charge-discharge cycles in the Land test system. The first low current constant current charge-discharge test was conducted at a rate of 0.1C, the constant current charge-discharge rate in the cycle test was set to 1C, the rate test ranged from 0.1C to 20C, and the voltage range was 2.0 to 4.0V.
[0139] The efficiency value is obtained by calculating the ratio of the 0.1C first discharge specific capacity to the 0.1C first charge specific capacity.
[0140] The test results of the electrochemical performance test of the sodium vanadium fluorophosphate positive electrode materials prepared in each embodiment and comparative example are listed in the following Table 2.
[0141] III. Test results of various embodiments and comparative examples Table 1
[0142]
[0143] Table 2
[0144]
[0145]
[0146] From the above content, it can be seen that by applying the technical solution of the present application, the sodium vanadium fluorophosphate positive electrode material contains a nitrogen-doped carbon coating layer, and the ratio of Ig and Id of the nitrogen-doped carbon coating layer in the Raman spectrum is controlled within the range of 1 to 1.9, and the porosity of the sodium vanadium fluorophosphate positive electrode material is controlled within the range of 12% to 33%, so that the nitrogen-doped carbon coating layer presents a relatively uniform porous network structure, which is conducive to effectively controlling the volume change and agglomeration of the sodium vanadium fluorophosphate particles during the charge and discharge process, thereby enhancing the structural stability of the sodium vanadium fluorophosphate positive electrode material. At the same time, the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material of the present application has the above-mentioned porous amorphous carbon coating structure and the introduction of nitrogen atoms, which is conducive to controlling the powder resistivity of the sodium vanadium fluorophosphate positive electrode material within the range of 27000Ω·cm to 73000Ω·cm, which helps to enhance the conductivity and ion diffusion of the sodium vanadium fluorophosphate positive electrode material, so that the sodium vanadium fluorophosphate positive electrode material has excellent electrochemical properties in terms of cycle performance and rate performance.
[0147] Specifically, it can be seen from the electrochemical performance test data in Table 2 that the main difference between Examples 1-5 of the present application and Comparative Examples 1-2 is that Comparative Examples 1 and 2 do not use spray freeze drying to dry the gel slurry, and there is no nitrogen-doped carbon coating layer formed by a uniform porous carbon aerogel network on the surface of the sodium vanadium fluorophosphate particles. The ion and electron transmission performance is poor, and the powder resistivity is high. Therefore, the rate performance and cycle performance of the sodium ion battery prepared by the positive electrode materials of these two comparative examples are far worse than those of the sodium vanadium fluorophosphate positive electrode materials prepared in Examples 1-5, especially under high rate charge-discharge conditions.
[0148] In Examples 1, 6 and 7, due to the different amounts of organic carbon source and organic nitrogen source added, it can be seen from the results of Table 1 and Table 2 that the carbon content and nitrogen content in the prepared sodium vanadium fluorophosphate positive electrode material are quite different. When the carbon and nitrogen contents in the sodium vanadium fluorophosphate positive electrode material are too low, due to the poor coating effect of the nitrogen-doped carbon coating layer, the electronic conductivity of the sodium vanadium fluorophosphate is low and the capacity is low; when the carbon content in the sodium vanadium fluorophosphate positive electrode material is too high, it is not conducive to ion transport, and the capacity of the finished sodium vanadium fluorophosphate positive electrode material is low; controlling the carbon and nitrogen elements in the sodium vanadium fluorophosphate positive electrode material within a certain range is beneficial to improving the capacity and cycle performance of the sodium vanadium fluorophosphate positive electrode material.
[0149] In Examples 1, 8 and 9, due to the different addition ratios of the organic nitrogen source and the organic carbon source, it can be seen from the results of Table 1 and Table 2 that the electrochemical properties of the obtained sodium vanadium fluorophosphate positive electrode material are affected. The carbon and nitrogen content in the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material is within a certain range, which can form a porous network structure that is more conducive to electron and ion conduction, thereby further improving the electrochemical properties of the sodium vanadium fluorophosphate positive electrode material.
[0150] Combining the results of Examples 10-12 and Example 1 in Tables 1 and 2, it can be seen that the particle size and specific surface area of the sodium vanadium fluorophosphate positive electrode material have a certain influence on its electrochemical performance. The diffusion path of sodium ions is related to the particle size of the positive electrode material. When the particle size is too large, it is easy to cause the sodium ion diffusion path to increase, resulting in a decrease in the electrochemical performance of the sodium vanadium fluorophosphate positive electrode material. When the particle size of the sodium vanadium fluorophosphate positive electrode material is too small, the specific surface area increases. The sodium vanadium fluorophosphate positive electrode material is easy to absorb water, which will make the positive electrode sheet difficult to dry and will also cause a decrease in electrochemical performance.
[0151] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A sodium vanadium fluorophosphate positive electrode material, characterized in that: The invention comprises sodium vanadium fluorophosphate particles and a nitrogen-doped carbon coating layer on the surface of the sodium vanadium fluorophosphate particles, wherein the ratio of Ig to Id of the nitrogen-doped carbon coating layer in Raman spectrum is 1 to 1.9, the porosity of the sodium vanadium fluorophosphate positive electrode material is 12% to 33%, and the powder resistivity of the sodium vanadium fluorophosphate positive electrode material is 27000 Ω·cm to 73000 Ω·cm.
2. The sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that The mass of the carbon element in the nitrogen-doped carbon coating layer accounts for 1% to 4% of the mass of the sodium vanadium fluorophosphate positive electrode material; The mass of the nitrogen element in the nitrogen-doped carbon coating layer accounts for 0.2% to 1.5% of the mass of the sodium vanadium fluorophosphate positive electrode material.
3. The sodium vanadium fluorophosphate positive electrode material according to claim 1 or 2, characterized in that: The D50 particle size of the sodium vanadium fluorophosphate positive electrode material is 0.8 μm to 14 μm, and the D100 particle size of the sodium vanadium fluorophosphate positive electrode material is less than 65 μm; The specific surface area of the sodium vanadium fluorophosphate positive electrode material is 12 m 2 / g~62m 2 / g; The average pore size of the nitrogen-doped carbon coating layer of the sodium vanadium fluorophosphate positive electrode material is 1.9 nm to 6 nm; The powder resistivity of the sodium vanadium fluorophosphate positive electrode material is 27500Ω·cm to 62000Ω·cm.
4. A method for preparing a sodium vanadium fluorophosphate positive electrode material, characterized in that: include: The sodium vanadium fluorophosphate, an organic carbon source, an organic nitrogen source and a cross-linking agent are mixed and gelled to obtain a gel slurry; The gel slurry is subjected to drying treatment and carbonization treatment to obtain the sodium vanadium fluorophosphate positive electrode material, and the drying treatment includes spray freeze drying.
5. The method for preparing the sodium vanadium fluorophosphate positive electrode material according to claim 4, characterized in that: The organic carbon source is one or more of carboxymethyl cellulose, starch, sucrose and cyclodextrin; The organic nitrogen source is one or more of chitosan and gelatin; The mass ratio of the organic carbon source to the organic nitrogen source is (1:1)-(3:1); The sum of the mass of the organic carbon source and the organic nitrogen source is 6%-18% of the mass of the sodium vanadium fluorophosphate.
6. The method for preparing the sodium vanadium fluorophosphate positive electrode material according to claim 4, characterized in that: The cross-linking agent is one or more of citric acid, tannic acid, tannic acid and phytic acid; The mass of the cross-linking agent is 15%-25% of the mass of the sodium vanadium fluorophosphate.
7. The method for preparing the sodium vanadium fluorophosphate positive electrode material according to any one of claims 4 to 6, characterized in that: The temperature of the gel treatment is 30° C.-50° C., and the time of the gel treatment is 2 h to 6 h.
8. The method for preparing the sodium vanadium fluorophosphate positive electrode material according to claim 4, characterized in that: The atomization pressure of the spray freeze drying is 0.1MPa-0.4MPa; The carbonization treatment includes a staged carbonization treatment, which sequentially includes a first stage carbonization treatment, a second stage carbonization treatment and a third stage carbonization treatment. The temperature of the first stage carbonization treatment is 100°C to 120°C, and the insulation time of the first stage carbonization treatment is 2h-4h. The temperature of the second stage carbonization treatment is 300°C to 350°C, and the insulation time of the second stage carbonization treatment is 1h-3h. The temperature of the third stage carbonization treatment is 600°C to 750°C, and the insulation time of the third stage carbonization treatment is 5-8h.
9. A positive electrode sheet, comprising a current collector and an active material layer disposed on the surface of the current collector, characterized in that: The active material layer comprises the sodium vanadium fluorophosphate positive electrode material according to any one of claims 1 to 3 or the sodium vanadium fluorophosphate positive electrode material prepared by the preparation method of the sodium vanadium fluorophosphate positive electrode material according to any one of claims 4 to 8.
10. A sodium ion battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 9.
Citation Information
Cited By
Positive electrode sheet for sodium-ion battery, and battery, battery pack and electric device
WO2026158105A1